WhatsApp as a Pedagogical Tool During COVID-19: A Bibliometric Review - Duh, Iwih; Makda, Fatima; Dlamini, Reuben (International Journal of Educational Development in Africa, 2025)
The COVID-19 pandemic triggered an abrupt shift to remote learning, which exacerbated existing inequities for disadvantaged students owing to limited internet connectivity, inadequate access to devices, and a less conducive learning environment at home. In this context, accessible digital platforms like WhatsApp became vital for maintaining educational continuity. This bibliometric review systematically analysed scholarly literature from the Scopus database to explore the use of WhatsApp as a pedagogical tool across all educational levels during the pandemic. The objective was to map global research trends, geographical distribution, and thematic clusters. After applying specific inclusion and exclusion criteria, the review analysed 234 articles published between 2019 and 2024. VOSviewer was used to visualise metrics including yearly publication counts, geographical contributions, and keyword co-occurrence networks. The findings highlight WhatsApp’s diverse use in facilitating interactivity and dialogic teaching, which is characterised by five core principles: collective, reciprocal, supportive, cumulative, and purposeful learning. This article provides valuable insights into leveraging accessible technology to enhance educational outcomes, dialogue and interactivity, specifically benefiting educators, policy makers, and curriculum developers in the post-pandemic era.